Decisional Regret and Financial Toxicity among Patients with Benign Renal Masses. Issue 1 (28th January 2022) - Mendhiratta, Neil; Sharma, Vidit; Wu, Jessica; Valdez, Tyler; Patel, Neal; Gottsleben, Debra; Battle, Dena; Saigal, Christopher; Shuch, Brian
Abstract: Introduction: Treatment of benign renal masses may often be unnecessary and can lead to significant morbidity, mortality, and health care costs. However, individual burdens such as decisional regret and financial costs associated with treatment are not well understood. Methods: Members of a support group who have been diagnosed with benign renal tumors were surveyed to evaluate demographic and clinical characteristics as well as decisional regret, using the modified Decision Regret Scale (DRS), and financial toxicity, using the Comprehensive Score for Financial Toxicity (COST). Predictors of decisional regret (DRS score >25) and financial toxicity were explored using logistic and linear regression analyses, respectively. Results: Of 70 respondents with complete data, 49 (70%) received definitive treatment while 21 (30%) elected surveillance. Decisional regret was expressed by 34/70 (49%) of patients and was associated with increasing age, smaller tumor size, and use of surveillance vs active treatment in univariable analysis. Patients reported significant financial toxicity from the diagnosis of a benign renal mass with a median COST score of 24, similar to a historical cohort of patients with stage IV solid organ cancers undergoing chemotherapy. Qualitative analysis of patient responses identified a lack of discussion by the provider of the likelihood of benign disease, postoperative complications, and financial burden as common themes in their experiences. Conclusions: High levels of decisional regret and financial toxicity were found among individuals with benign renal lesions regardless of treatment approach. Improved counseling and diagnostic tools may limit the psychological and financial burdens from these benign entities.